Impaired Cell Viability and Functionality of Hepatocytes After Incubation With Septic Plasma—Results of a Second Prospective Biosensor Study - Sauer, Martin; Haubner, Cristof; Richter, Georg; Ehler, Johannes; Mencke, Thomas; Mitzner, Steffen; Margraf, Stefan; Altrichter, Jens; Doß, Sandra; Nöldge-Schomburg, Gabriele (Frontiers in Immunology, 2018)
Early diagnosis of liver- dysfunction and failure can enable early onset of therapy and lead to an improvement of prognosis of these patients. Nearly 19% of patients with septic shock developed a liver dysfunction in the course of disease. To verify the clinical relevance of a new cell-based test device (biosensor), we conducted a second study with septic patients. We have developed a test device for (early) diagnosis of liver failure. The basic test compounds consist of human liver cells (HepG2/C3A). In a standardized microtiterplate assay toxicity of patient plasma is tested. After incubation time of 72 hours, viability of cells (XTT test, trypanblue-staining), cytochrome 1A2 activity (metabolism of ethoxyresorufine), and synthesis of albumin are measured. In a prospective clinical study in 99 ICU-patients two test groups were investigated: the septic group (n=51, SG), and the control (non-septic) group (n=49, CG). At time of inclusion, after 3, and 7 days, 10 ml blood was drawn from the patients for testing with the cytotoxicity test. Patients followed up to hospital survival, and organ functions; demographic data, illness severity (APACHE II-, SOFA-scores, cytokines, circulating-free deoxyribonucleic acid/neutrophil derived extracellular traps (cf-DNA/NETs), microbiological results, and pre-morbidity were recorded. The in-hospital mortality was 23.5 % in the SG. Two patients of the CG died. The APACHE II-scores at ICU arrival was 32 in the SG, and 9 in the CG, the SOFA-scores at inclusion were 13 in the SG, and 2 in the CG. The values of bilirubin (SG-Survivors: 19.2 µmol/l, SG-Non-Survivors: 21.4, CG: 15.2) were significantly higher than in the CG at inclusion, and the values of cf-DNA/NETs were significantly higher in the SG at inclusion, after 3, and after 7 days. The plasma of patients with sepsis impaired significantly viability and cellular functions of HepG2/C3A cells compared with the plasma of non-septic patients; these effects were more pronounced with plasma of non-survivors in the SG compared with survivors at inclusion. The presented liver cell-based biosensor showed hepatotoxicity of plasma at inclusion and in the course of disease in patients with septic shock in a second biosensor study.